A hybrid preventive maintenance model for systems with partially observable degradation. (6th February 2020) - Finkelstein, Maxim; Cha, Ji Hwan; Levitin, Gregory
Abstract: A new model of hybrid preventive maintenance of systems with partially observable degradation is developed. This model combines condition-based maintenance with age replacement maintenance in the proposed, specific way. A system, subject to a shock process, is replaced on failure or at some time T_S if the number of shocks experienced by this time is greater than or equal to m or at time T>T_S otherwise, whichever occurs first. Each shock increases the failure rate of the system at the random time of its occurrence, thus forming a corresponding shot-noise process. The real deterioration of the system is partially observed via observation of the shock process at time T_S . The corresponding optimization problem is solved and a detailed numerical example demonstrates that the long-run cost rate for the proposed optimal hybrid strategy is smaller than that for the standard optimal age replacement policy.